The IGF signalling factors during chick limb muscle development - Mohammed, Rabeea Hazim (2017)
In vertebrates, muscle precursor cells delaminate and migrate from the somites into the limb, where they proliferate and differentiate to muscle masses. Many transcription factors, including Pax and the myogenic regulatory factors (Mrfs) play a vital role in regulating limb muscle growth and development. In the limb, the progenitors begin the process of myogenesis by expressing the myogenic determination factors Myf5 and MyoD, and differentiation factors Myog and Mrf4 then eventually form dorsal and ventral skeletal muscle masses. However, the role of insulin-like growth factors (IGFs) in regulating the early processes of limb myogenesis, and the functional relevance of IGF-1 and IGF-2 in myogenic determination remains poorly defined. By whole-mount in situ hybridisation (WISH), the present study first characterised the expression of both Mrfs and components of the IGF in chick limbs at precise stages during embryonic development. The analysis of the spatial and temporal expression patterns of both Mrfs and IGFs allowed further interventions to be precisely targeted. Therefore, to determine the mechanism of how these factors interact, application of IGF-soaked beads into chick limb during the development was followed by analysis of muscle specific marker genes. Both Pax3 and MyoD were selected as markers for undifferentiated and differentiated myogenic cells respectively. First, the present study demonstrated both IGF-1 and IGF-2 as novel players in early limb myogenesis in vivo by stimulating the activation of Pax3 and MyoD expression. IGF-1 was also shown to increase numbers of both Pax3+ve and mitotic cells, but not the numbers of mitotic Pax3+ve cells, suggesting the increase in Pax3 expression was not simply via increased proliferation. IGF signalling was then examined using picropodophyllotoxin (or PPP) as a specific inhibitor of the IGF-1 receptor. The present data showed that blocking of IGF-1R with PPP inhibited both IGF-1 and IGF-2 induced expression of both Pax3 and MyoD. To confirm the mechanisms for the effects of the IGFs, the current study also used a panel of pharmacological inhibitors, such as U0126 and LY294002 to block the mitogen activated protein kinase (MAPK) and AKT signalling pathways, respectively as well as Nocodazole to inhibit cell proliferation. Results showed that the effects of both IGF-1 and IGF-2 on Pax3 and MyoD expression were mediated by the MAPK pathway. In contrast, inhibition of the AKT signalling pathway inhibited IGF-2 (but not IGF-1) stimulated Pax3 expression, as well as IGF-1 (but not IGF-2) stimulated MyoD expression. Inhibition of cell proliferation with Nocodazole had no effect on IGF-1 stimulated Pax3 or MyoD expression. Similarly Nocodazole had no effect on IGF-2 stimulated Pax3 expression, whereas it inhibited IGF-2 stimulated MyoD expression. SU5402, an inhibitor of FGF receptor, showed no effect on IGF-1 and IGF-2 stimulated Pax3 expression whereas it inhibited their stimulation of MyoD. These findings led to the proposal of a model where IGF signalling directs the timing of the early steps of myogenic cells by stimulating Pax3 expression, whereas the upregulation in MyoD expression is indirectly controlled via Fgf. Together, these results give new insights into the early embryonic development of limb muscle in birds. Additionally, a deeper knowledge of a specific interaction between IGFs and Mrfs may well provide a molecular basis for preventing the loss of muscle and muscle diseases in animals and humans. The present study may well also shed a light to improve the production of chicken meat.